High‐Performance Flexible Pressure Sensor with a Self‐Healing Function for Tactile Feedback. Issue 20 (15th April 2022) - Yang, Mei; Cheng, Yongfa; Yue, Yang; Chen, Yu; Gao, Han; Li, Lei; Cai, Bin; Liu, Weijie; Wang, Ziyu; Guo, Haizhong; Liu, Nishuang; Gao, Yihua
Abstract: High‐performance flexible pressure sensors have attracted a great deal of attention, owing to its potential applications such as human activity monitoring, man–machine interaction, and robotics. However, most high‐performance flexible pressure sensors are complex and costly to manufacture. These sensors cannot be repaired after external mechanical damage and lack of tactile feedback applications. Herein, a high‐performance flexible pressure sensor based on MXene/polyurethane (PU)/interdigital electrodes is fabricated by using a low‐cost and universal spray method. The sprayed MXene on the spinosum structure PU and other arbitrary flexible substrates (represented by polyimide and membrane filter) act as the sensitive layer and the interdigital electrodes, respectively. The sensor shows an ultrahigh sensitivity (up to 509.8 kPa –1 ), extremely fast response speed (67.3 ms), recovery speed (44.8 ms), and good stability (10 000 cycles) due to the interaction between the sensitive layer and the interdigital electrodes. In addition, the hydrogen bond of PU endows the device with the self‐healing function. The sensor can also be integrated with a circuit, which can realize tactile feedback function. This MXene‐based high‐performance pressure sensor, along with its designing/fabrication, is expected to be widely used in human activity detection, electronic skin, intelligent robots, and many other aspects. Abstract : A MXene‐based high‐performance flexible piezoresistive sensor is fabricated by a simple spraying method. Due to the abundant hydrogen bonds of polyurethane, the pressure sensor owns a self‐healing function. By integrating the flexible piezoresistive sensor with manipulator, resistance–voltage converter, SGS‐THOMSON Microelectronics (STM) 32 microprogrammed control unit signal analysis unit, and touchscreen, a tactile feedback system is achieved.